1995
DOI: 10.1021/ef00049a006
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Reactions During Plasma Arcing of Carbonaceous Materials

Abstract: Fullerene and pencil production has been studied by electrical arcing in various atmospheres. A range of different materials have been used as anode and the products have been studied using high-pressure liquid chromatography, gas chromatography-mass spectrometry, stable isotope mass spectrometry, and electron and light microscopy. In a methane atmosphere with graphite, the residual methane carbon is isotopically heavy because lighter methane is consumed. A different result is obtained with anodes containing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Figure 11 shows TEM micrograph of Samla SCC showing CNT of about 6-8 nm diameter and nanoparticles. (32) had also made the similar observations in their studies on the production of CNTs from coal. It also has been found that Assam coal produced spherical nanoparticles of comparatively larger size than those obtained from other coal samples (Fig.…”
Section: Development Of Catalyst Free Carbon Nanotubes 571supporting
confidence: 53%
“…Figure 11 shows TEM micrograph of Samla SCC showing CNT of about 6-8 nm diameter and nanoparticles. (32) had also made the similar observations in their studies on the production of CNTs from coal. It also has been found that Assam coal produced spherical nanoparticles of comparatively larger size than those obtained from other coal samples (Fig.…”
Section: Development Of Catalyst Free Carbon Nanotubes 571supporting
confidence: 53%
“…This was not observed, yet, their supposed contribution to G would rapidly decrease with the rst curing steps, since these molecules are highly volatile under laser radiation 46 and they can be incorporated in further tube growth. 47 Again, to circumvent the inaccuracies that may accompany the I D /I G + ratio, I G 0 /I D complements the characterisation. These two parameters, common indicators of defect and purity states, experience a 92% and 1180% improvement (at I 1 ), respectively, with respect to the pristine material (at I 0 ).…”
Section: Inuence Of Laser Powermentioning
confidence: 99%
“…That is, all bonds in the processed material do not have to be broken during arcing. We have recent confirmation of this mechanism from plasma arcing experiments using naphthalene as fill in hollow graphite tubes in order to simulate the way fullerenes and nanotubes might be formed from polycyclic hydrocarbons in coaI 9 ,1O. The results show that naphthalene in the plasma arc fringe increases the C70 to C60 fullerene ratio in the product soot and also increases the void space in the formed multiwalled nanotubes.…”
Section: Introductionmentioning
confidence: 83%